Simultaneous determination of Cd(II) and Pb(II) using square wave anodic stripping voltammetry at a gold nanoparticle-graphene-cysteine composite modified bismuth film electrode - Zhu, Lian; Xu, Lili; Huang, Baozhen; Jia, Ningming; Tan, Liang; Yao, Shouzhuo (Electrochimica acta, 2014)
A sensitive platform for the simultaneous electrochemical determination of Cd(II) and Pb(II) in aqueous solution has been developed based on the gold nanoparticle-graphene-cysteine composite (Au-GN-Cys) modified bismuth film glassy carbon electrode (GCE) using square wave anodic stripping voltammetry (SWASV). The synergistic effect of cysteine as well as the enlarged, activated surface and good electrical conductivity of gold nanoparticles and graphene contributed to the deposition of Cd(II) and Pb(II) on the electrode surface. Under the optimum conditions, a linear relationship existed between the currents and the concentrations of Cd(II) and Pb(II) in the range between 0.50μgL−1 to 40μgL−1 with the detection limits of 0.10μgL−1 for Cd(II) and 0.05μgL−1 for Pb(II), respectively, based on a signal-to-noise ratio equal to 3 (S/N=3). The interference experiments show that some metal cations had little influence on the SWASV signals of Cd(II) and Pb(II). In addition, the developed electrode displayed a good repeatability and reproducibility. These studies imply that the Au-GN-Cys composites might be an alternative candidate for practical applications in electrochemical detection of metal ions.